Service Quality Management Dimensions and Its Effect on The Students’ Satisfaction: An Empirical study Amongst Secondary Schools in Pakistan - Muhammad Naveed Jabbar; Fauzi Hussin; Khalid Javeed Assi (Universitas Muhammadiyah Sidoarjo, 2020)
Because the cost of attracting the fresh customers is much advanced than cost of retaining current and old customers, possession on students’ satisfaction has become scorching debate in modern era. Service quality management plays its vital role for this concern. This current research paper aims to highlight the concepts of service quality management dimensions and its effect on students’ satisfaction. In this study, the dependent variable was students’ satisfaction that measured by the independent variable service quality. The secondary school students of public and private education institutions were the population of this study in Punjab Pakistan. Random sampling approach applied for the delimitation of the population. Sample was 727 students (public 345, private 382). Five point Likert scale used in questionnaire for the collection of data. This study adopted from Parasuraman’S SERVEQUAL dimensions model (1991). The test applied for analysis: Descriptive analysis, Factor analysis, independent sample t-test and Pearson Correlation. The findings of the study show that the quality of the public secondary schools was better as compare to private school. The correlation was resulted between .7 to .8, It shows that there was a significance effect of service quality management on students’ satisfaction. The paper provides the guidance for sort out the most effective factors about the customers’ satisfaction regarding service quality. This research study will prove as a stepping-stone for the development of the managerial strategies. It will also helpful for educational leaders, policy makers and head of the department for the development of quality education.